2009
DOI: 10.1177/0269216309104892
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of two decision-making scales for children with life-limiting illnesses

Abstract: Purpose Annually, about 500,000 children are coping with life-limiting illnesses. Many of these children could benefit from pediatric palliative care which provides supportive services. These services can also aid parents in decision making. In order to measure the effect of pediatric palliative care programs on decision making, a valid and reliable tool must be identified. This study aims to validate the psychometric properties of the Decisional Conflict Scale (DCS) and the COMRADE instruments for children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
1
21
0
4
Order By: Relevance
“…A systematic literature review of CPC in sub-Saharan Africa undertaken in 201033 found only five papers in peer-reviewed journals, four reporting on service evaluation (one with quantitative outcomes,43 three others an evaluation of activity and process31 44 45 and one a programmatic description from two countries: South Africa and Uganda46). The authors suggested the lack of evidence was partly attributable to the challenges in undertaking CPC research, as well as the fact that few reliable, valid and developmentally appropriate methods are available 33 47.…”
Section: Status Of the Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review of CPC in sub-Saharan Africa undertaken in 201033 found only five papers in peer-reviewed journals, four reporting on service evaluation (one with quantitative outcomes,43 three others an evaluation of activity and process31 44 45 and one a programmatic description from two countries: South Africa and Uganda46). The authors suggested the lack of evidence was partly attributable to the challenges in undertaking CPC research, as well as the fact that few reliable, valid and developmentally appropriate methods are available 33 47.…”
Section: Status Of the Sciencementioning
confidence: 99%
“…Priorities for CPC research generally are varied, with research in HICs focusing on issues such as service evaluation,50–52 decision making,46 53 the impact of educational programmes,54 55 telehealth,56 57 preferred place of death,58 resource utilisation and costs,59 60 pain management,40 61 perinatal palliative care,62 screening for palliative care,63 64 and quality-of-life measures 65…”
Section: Status Of the Sciencementioning
confidence: 99%
“…[17][18][19][20] The IOF was developed to measure the impact of children's illnesses on families, but has also been used with families of children with life-threatening illnesses. 13,14 The scale includes 15 items assessing various aspects of family stress and strain in various settings. Response categories for individual items are ''strongly disagree,'' ''disagree,'' ''agree,'' and ''strongly agree.''…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents in the intervention felt better about their decisions. 12 A study by Knapp and colleagues 13 compared the performance of two decisional conflict scales with 266 parents of children with life-threatening illnesses. Results from the study suggest that the Decisional Conflict Scale (DCS) is a valid and reliable instrument for this population.…”
mentioning
confidence: 99%
See 1 more Smart Citation